Analisis Butir Soal Berpikir Kritis Fisika pada Materi Kisi Difraksi dengan Model Rasch - Kusniati, Rani; Rosana, Dadan; Istiyono, Edi (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
This study aims to analyze the quality of a physics critical thinking test focused on the topic of diffraction grating using the Rasch model, with the aid of QUEST software. The research employed an evaluative methodology with a descriptive quantitative approach. The subjects consisted of 30 eleventh-grade students from SMA Budi Mulia Dua Yogyakarta. The test instrument comprised 10 multiple-choice physics questions, which were developed and validated in collaboration with physics teachers. These questions specifically addressed the concept of diffraction grating, aiming to measure students’ critical thinking skills in that domain including interpretation, analysis, evaluation, inference, and explanation. Data analysis was conducted using the Rasch model via QUEST software to evaluate item fit, reliability, and consistency. The results showed that 8 out of the 10 items had INFIT MNSQ values ranging from 0.77 to 1.33, indicating a good fit with the Rasch model. However, items 6 and 9 were found to have INFIT MNSQ values outside the acceptable range, suggesting that they were misfitting and should be revised and refined to better align with the intended construct. Despite this, the items may be revised for future use. The OUTFIT t values for all items were ≤ 2.00, confirming their usability. Additionally, the item reliability estimate was 0.84 and the case reliability estimate was 0.56, demonstrating high internal consistency and indicating that the test is suitable for measuring students' critical thinking skills in physics